Raising the Achievement of All Learners in Inclusive Education – Literature Review (European Agency for Special Needs and Inclusive Education)
The Raising the Achievement of All Learners in Inclusive Education (RA) project (2014–2017) aimed to provide evidence of effective practice in raising achievement by building the capacity of schools and communities to include and support all learners.

(untitled) - Kefallinou, Anthoula (2016)